Theory appraisal in Islamic economic methodology: purposes and criteria - Furqani, Hafas; Haneef, Mohamed Aslam (Emerald Group Publishing, 2012)
Purpose – The purpose of this paper is to attempt to investigate the conceptual foundations of methodological inquiry in Islamic economics. The paper aims to develop criteria of acceptance and rejection of a theory and providing rationalizations and guidelines in the process of theory appraisal and evaluation. Design/methodology/approach – The literature on Islamic economics especially in the area of methodology of Islamic economics, both in English and Arabic, is reviewed critically and used in the attempt of constructing the criteria of theory appraisal in Islamic economics. Findings – The paper explicates two criteria of theory appraisal in Islamic economics, namely the internal-integrity (doctrinal integrity, logical integrity and factual integrity) and relational-unity(of doctrine and practical realities, ideals/goals and factual experiences, values and facts, normative and positive dimensions, a priori and a posteriori). Research limitations/implications – The paper is based on conceptual explorations of literature in the area of methodology of Islamic economics. This is a conceptual paper, so it did not employ any empirical analysis. Practical implications – The findings of this paper will give insights of the criteria to distinguish truth over false notions in theories, between valid theories and invalid ones as well as the acceptance or rejection of theory in Islamic economics theory appraisal. With those criteria of theory, a unified discipline of Islamic economics, which is based on doctrinal, logical on testable foundations in a real typical Muslim society can be produced. Originality/value – The paper proposes criteria and purpose of theory appraisal in Islamic economics which is lacking in the discussion of methodology of Islamic economics literature. Those criteria and purpose in theory appraisal and evaluation in a methodological unity of Islamic economics suggest a new approach in dealing with revelation, intellectual reasoning and facts observation in order to produce a coherent Islamic economic theory. Keywords Methodology of Islamic economics, Tawhidic methodology, Theory appraisal, Theory evaluation, Criteria, Framework, Islam, Economics Paper type - Conceptual paper